2022
DOI: 10.3389/fimmu.2022.915218
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microflora Modulates Th17/Treg Cell Differentiation in Experimental Autoimmune Prostatitis via the Short-Chain Fatty Acid Propionate

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a very common urological disorder and has been gradually regarded as an immune-mediated disease. Multiple studies have indicated that the gut microflora plays a pivotal part in immune homeostasis and autoimmune disorder development. However, whether the gut microflora affects the CP/CPPS, and the underlying mechanism behind them remain unclear. Here, we built an experimental autoimmune prostatitis (EAP) mouse model by subcutaneous immunity and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…And they found fecal bacteria transplants from EAP mice, but not from control mice, into the pseudo‐germ‐free mice, significantly exaggerated host depression‐like behaviors [ 67 ] . Additionally, Du et al found that gut dysbiosis contributed to a Th17/Treg differentiation imbalance in EAP mice via the decrease of metabolite propionic acid [ 68 ] . Recently, a novel diagnostic model for CP/CPPS based on different gut microbiome compositions was proposed, presenting the promising potential of gut microbiome for noninvasive diagnostic biomarkers and future therapeutic targets for CP/CPPS patients [ 69 ] .…”
Section: Resultsmentioning
confidence: 99%
“…And they found fecal bacteria transplants from EAP mice, but not from control mice, into the pseudo‐germ‐free mice, significantly exaggerated host depression‐like behaviors [ 67 ] . Additionally, Du et al found that gut dysbiosis contributed to a Th17/Treg differentiation imbalance in EAP mice via the decrease of metabolite propionic acid [ 68 ] . Recently, a novel diagnostic model for CP/CPPS based on different gut microbiome compositions was proposed, presenting the promising potential of gut microbiome for noninvasive diagnostic biomarkers and future therapeutic targets for CP/CPPS patients [ 69 ] .…”
Section: Resultsmentioning
confidence: 99%
“…[81] and Akkermansia muciniphila (A. muciniphila) [82] can also induce RORγt + Treg cell-mediated immune responses. Comparatively, lowered levels of the gut-microbiota-derived metabolite propionate (a short chain fatty acid) can contribute to a pathological imbalance in the Th17/Treg cell differentiation [83,84].…”
Section: Interaction Between Gut Microbiota and Adaptive Immune Systemmentioning
confidence: 99%
“…Finally, it has been reported that SCFA and gut microbiota populations, which are great producers of these fatty acids, such as Clostridium , Faecalibacterium , or Roseburia , among others, [ 40 ] present lower levels in patients with IBD [ 41 , 42 , 43 ] as well as in patients with MS [ 44 , 45 , 46 , 47 ] or colorectal cancer [ 48 , 49 , 50 ] compared to healthy individuals. Their beneficial effect has also been demonstrated in experimental models such as colitis [ 25 , 32 , 51 ], experimental autoimmune encephalomyelitis (EAE) [ 33 , 52 ], allergic asthma [ 53 ], arthritis [ 51 , 54 ], and prostatitis [ 55 ], among others. Thus, this positive effect that has been partly attributed to the induction of Treg cells could be translated into the clinic, and in fact, a few clinical trials have shown some preliminary but encouraging results [ 56 , 57 , 58 ].…”
Section: Gut Microbiota-derived Metabolites: Effect On Th17/treg Bala...mentioning
confidence: 99%